-7(k+9)=9(k+-5)+-14k

Simple and best practice solution for -7(k+9)=9(k+-5)+-14k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(k+9)=9(k+-5)+-14k equation:



-7(k+9)=9(k+-5)+-14k
We move all terms to the left:
-7(k+9)-(9(k+-5)+-14k)=0
We add all the numbers together, and all the variables
-7(k+9)-(9(k-5)+-14k)=0
We use the square of the difference formula
-7(k+9)-(9(k-5)-14k)=0
We multiply parentheses
-7k-(9(k-5)-14k)-63=0
We calculate terms in parentheses: -(9(k-5)-14k), so:
9(k-5)-14k
We add all the numbers together, and all the variables
-14k+9(k-5)
We multiply parentheses
-14k+9k-45
We add all the numbers together, and all the variables
-5k-45
Back to the equation:
-(-5k-45)
We get rid of parentheses
-7k+5k+45-63=0
We add all the numbers together, and all the variables
-2k-18=0
We move all terms containing k to the left, all other terms to the right
-2k=18
k=18/-2
k=-9

See similar equations:

| 8-4(f-3)=0 | | -7(k+9)=9(k+-5)-14k | | 5+7x+x=1+7x+1 | | 14n=-126 | | -7(x+6)-3(3x-3)=-65 | | 9k-16=52 | | g+143=1000 | | 33/4=r=1/8 | | №23x=10 | | 4z-3(z-6)=3=2z | | -4m-8=54 | | 2-2m=-20 | | 14-x=4+2x | | 21=-7×n | | 28j=952 | | 95x-15=-12 | | -27d=270 | | -8(8x-7)=440 | | 4^5x-9=(1/27)^2x-8 | | 5(3-e)+10=0 | | h+577=952 | | 8/11n=64 | | X=1+1.2x | | -10k+6k+k×10=60 | | 8/11n=74 | | y-52=174 | | 3x+-9=(10+x) | | 8(7-2x)=104 | | -3c+8-5c=-26 | | m-19=18 | | -2p-8+9p=4+13p | | -(3/4)*x=-(5/8) |

Equations solver categories